Land use planning and climate change. Dogmatic and critical study of the Regional Land Management Plan in Chile - Delooz Brochet, Benoît; Serrano Moreno, Juan Enrique (Revista de Derecho Ambiental, 2023)
The Regional Land Management Plan (PROT) is an administrative planning instrument introduced in Chile in 2018 by Law n. 19.175, constitutional organic law on regional government and administration, whose national policy has been adopted in 2021 and whose regulations are under development. In the framework of the Chilean regionalization process, the legislator sought with the PROT to decentralize to the regions key administrative planning competences for sustainable development and the climate crisis. The instrument is regulated by a regulatory framework largely composed of recently adopted norms that have not been fully implemented, in particular due to the recent introduction by the Climate Change Framework Law of 2022, of the climate variable in numerous administrative procedures. The introduction of the latter impacts the creation, adoption and implementation of the PROT creating new duties for the Administration and making procedures more complex. This study, based on a dogmatic and critical analysis of the set of norms that regulate the PROT, argues that the absence of a stable and coherent regulatory framework, as well as the increase in conflicts between public entities, represent major obstacles to the fulfillment of the objectives of the instrument in terms of prevention and mitigation of the effects of climate change.